Elements for the determination of the beautiful thing in Plato fs dialogues (Iter, 2022)
The relevance of the notion of "beauty " in the socratic-platonic tradition is an nncontestedtopic. However. how can u e describe objects. events. discourses as beautiful without knowirtgwhat "beauty " means?In this paper. I revise Plato s early reflections on beauty without considering Plato s laterw orks in which the concept is just used rather than defined.Initially Plato s notion of "beauty " is unresolved and everyday language. as exempliftedby Hippias. is used to describe concrete situations. But later. Plato follows Sócrates' definitionas an effort to find a common notion of the concept. Finally. Plato s notion of "beauty " istransposed to the notion of idea.
Keywords: Beauty. beautiful. proportion. measure. order